2018
DOI: 10.33407/itlt.v64i2.1979
|View full text |Cite
|
Sign up to set email alerts
|

Влияние Технологии Webquests На Успешность Формирования Навыков Чтения И Письма Студентов Университета

Abstract: WebQuests are increasingly becoming popular in teaching English as a foreign language since they provide learners with authentic and collaborative tasks. The aim of this study was to explore whether using WebQuests is effective in enhancing writing and reading performance of students at a university level. The experimental groups were taught through traditional instruction with the elements of WebQuests as additional reading and writing activities. The control groups had the traditional ESL lessons only. Signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
3
4
0
Order By: Relevance
“…They enjoyed working with their peers to complete the learning tasks. These findings are compatible with the findings on using WebQuest to enhance English writing and reading performance, conducted by Berezova et al (2018). They found that the students were actively engaged with the authentic and collaborative tasks provided through the Internet.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…They enjoyed working with their peers to complete the learning tasks. These findings are compatible with the findings on using WebQuest to enhance English writing and reading performance, conducted by Berezova et al (2018). They found that the students were actively engaged with the authentic and collaborative tasks provided through the Internet.…”
Section: Discussionsupporting
confidence: 90%
“…Given the technological advancements in recent years, conducting research on the application of technology in teaching that had been done over the past ten years, and integrating online technology into the learning process were found to have a positive influence on the students' learning engagement (Dunlap & Lowenthal, 2018;Bognar, Sablic & Skugor, 2019). In order to improve the teaching methods and classroom environment, many educational institutions use new technology (e.g., tech-based learning) as part of their language classrooms (Berezova, Mudra & Yakushko, 2018;Dousti, Amirian & Nejadansari, 2021). Technology has the potential to offer quite a number of free learning materials online for learning activities (Teng, 2017;Gao, Shen & Wang, 2020).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…[24]. L. Berezova and co-authors propose to use Web Quests for improving writing students' abilities [25]. In our recent papers we also describe the experience of using informational technology tools [26; 27; 28] in teaching English.…”
Section: Introductionmentioning
confidence: 99%